DNA Amplifications and Aneuploidy, High Proliferative Activity and Impaired Cell Cycle Control Characterize Breast Carcinomas with Poor Prognosis - Harald Blegen; John S. Will; B. Michael Ghadimi; Hesed‐Padilla Nash; Anders Zetterberg; Gert Auer; Thomas Ried (Analytical Cellular Pathology)
In order to explore whether specific cytogenetic abnormalities can be used to stratify tumors with a distinctly different clinical course, we performed comparative genomic hybridization (CGH) of tumors from patients who were diagnosed with metastatic disease after an interval of less than 2 years or who remained free from distant metastases for more than 10 years. All patients presented with distant metastases after mastectomy indicating that none of the patients in this study was cured and free of remaining tumor cells. Tumors in the group of short‐term survivors showed a higher average number of chromosomal copy alterations compared to the long‐term survivors. Of note, the number of sub‐chromosomal high‐level copy number increases (amplifications) was significantly increased in the group of short‐term survivors. In both short‐ and long‐term survivors recurrent chromosomal gains were mapped to chromosomes 1q, 4q, 8q, and 5p. Copy number changes that were more frequent in the group of short‐term survivors included gains of chromosome 3q, 9p, 11p and 11q and loss of 17p. Our results indicate that low‐ and high grade malignant breast adenocarcinomas are characterized by a specific pattern of chromosomal copy number changes. Furthermore, immunohistochemical evaluation of the expression levels of Ki‐67, p27KIP1, p21WAF1, p53, cyclin A and cyclin E revealed a correlation between increased proliferative activity and poor outcome.